Integrating Emerging Technologies to Strengthen Montessori Preschool Learning - Mardhalia Saitakela; Dimas Aditya Prabowo; Lily Maria; Triyono (Jurnal MENTARI: Manajemen, Pendidikan dan Teknologi Informasi, 2026)
In the context of rapidly evolving educational technologies, Montessori preschool learning requires developmentally appropriate innovations that preserve hands-on exploration while enhancing children’s cognitive and sensorial growth. This study aims to investigate the integration of emerging technologies such as AI-assisted learning applications, multimodal digital storytelling, and sensor-based interactive materials within Montessori environments to understand how these tools can support autonomy, concentration, and individualized learning rhythms. The approach focuses on a qualitative case study involving classroom observations, teacher interviews, and analysis of children’s learning behaviours, with a total of 206 participants, to capture how technology is adopted and adapted in authentic preschool contexts. Findings indicate that technology aligned with Montessori principles increases engagement with sensorial tasks, enriches exploration, strengthens differentiated learning pathways, and provides teachers with accurate insight into developmental progress, although excessive digital exposure may reduce children’s interaction with concrete materials. Therefore, the study concludes that thoughtfully integrated emerging technologies can serve as a natural extension of Montessori learning when applied moderately, grounded in pedagogical intention, and designed to enhance rather than replace physical and self-directed experiences, ultimately demonstrating that balanced integration offers meaningful benefits for young learners.